Studies on Mixed Ligand Complexes of Lanthanide(III) Ions - Rajendran, G.; Usha Devi, K.G. (Asian Journal of Chemistry, 2010)
As part of our research programme, we have prepared and characterized a few nitrato, thiocyanato and perchlorato complexes of lanthanide(III) ions with ligands, viz., a Schiff base derived from p-anisidine and vanillin and diphenyl sulphoxide. The complexes were characterized by the measurement of electrical conductances and magnetic susceptibilities, molecular mass and metal percentage and spectral analysis. The thermal decompositions were studied by TG and DTG techniques. The thiocyanato complexes were prepared by substitution method from nitrato complexes. p-Anisidine-vanillin (HDDA) and diphenyl sulphoxide (DPSO) are coordinated to the metal ion in unidentate fashion. All the anions were involved in coordination in these complexes. Thus they were found to have non-electrolytic behaviour with composition [Ln(HDDA)2(DPSO)X3] where X = NO–3 or SCN–. Perchlorato complexes were prepared from metal perchlorate as done in the case of nitrato complexes. They were found to have electrical conductance which corresponds to 1 : 1 electrolyte. Hence one of the perchlorate ions is outside the coordination sphere. The composition of this complex is found to be [Ln(HDDA)3(DPSO)(ClO4)2]ClO4.